Self-assembled Reduced Graphene Oxide Films at a Liquid-air Interface - ZHANG Guang-yu; WANG Xin; XU Rui; LIU Lin-jing; LI Chuang; LvYin-lin; CHEN Yu-juan; ZHU Da-fu; YANG Xin-rui (Journal of Harbin University of Science and Technology)
In order to obtain the reduced graphene oxide film electrodes with superior performance, graphene oxide films were prepared by a method of self-assembled at a liquid-air interface with graphene oxide dispersion as raw material, polyethylene imine as binder. The reduced graphene film electrodes were obtained by hydroiodic acid. The film electrodes were characterizated using scanning electron microscopy, atomic force microscopy image, X-ray diffraction and X-ray photoelectron spectroscopy. The results showed that the reduced graphene films had good surface morphologies, uniform thickness and a carbon to oxygen atomic ratio of the reduced graphene films can achieve 10.2 after HI acid reduction. When the concentration of GO dispersion was 1.5mg/ml, the reduced graphene film electrodes had an electrical conductivity as high as 495.44 Scm-1.This study provides experimental basis for the application of electrode materials in micro/nano electronic devices.